Modern organisational governance - Crowther, David; Seifi, Shahla (Emerald Publishing Limited, 2017)
It is apparent that all forms of organisation have governance requirements and procedures but too often we just consider governance in a corporate environment. Equally it is accepted that the concept of governance is concerned with the relationship between the organisation and all of its stakeholders but is too often interpreted as a concern for the relationship between a corporation and its investors. Still this is essentially true as far as most corporations are concerned. Such narrow views are unrealistic and are inappropriate in the modern global world which we inhabit and many would blame problems with governance for the economic and financial turmoil which the world has experienced during the last decade. Much analysis has been undertaken about governance but little in the way of change is manifest and few seem to recognise both the need to consider radical changes in the modern global environment and the opportunities and possibilities presented by the current environment. In this book therefore we take a broad (and possibly radical) approach and consider governance requirements in the modern world - not just for corporations but for all forms of organisation.
Includes index.
Keywords: Corporate governance.; Economics.; Business & Economics -- Development -- Business Development.; Economics, finance, business & management.; elektronické knihy; electronic books